Development and standardization of solid phase assays for the detection of anti-neutrophil cytoplasmic antibodies (ANCA) A report on the second phase of an international cooperative study on the standardization of ANCA assays - Hagen, E. Christiaan; Andrassy, Konrad; Csernok, E.; Daha, M. R.; Gaskin, G.; Gross, W. L.; Hansen, B.; Heigl, Z.; Hermans, J.; Jayne, D.; Kallenberg, C. G. M.; Lesavre, Ph.; et al. (Journal of immunological methods, 1996)
Anti-neutrophil cytoplasmic antibodies (ANCA) are diagnostic markers for systemic vasculitis. They are classically detected by an indirect immunofluorescence test using normal donor neutrophils as substrate. This assay lacks antigenic specificity and is not quantitative. The ‘EC/BCR Project for ANCA Assay Standardization’ is an international collaboration study with the aim to develop and standardize solid phase assays for ANCA detection. In this part of the study the isolation and characterization of proteinase-3 and myeloperoxidase, the two main target molecules for ANCA, and the development and standardization of ELISAs with these antigens are described. Six laboratories successfully isolated purified proteinase-3 preparations that could be used. Three of these preparations, together with one myeloperoxidase preparation, were subsequently used for ANCA testing by ELISA. The ELISA technique was standardized in two rounds of testing in the 14 participating laboratories. The coefficient of variation of these new assays decreased from values of approx. 50% in the first round to approx. 20% in the second round. We conclude that purified proteinase-3 and myeloperoxidase can be used in standardized ELISAs for ANCA detection. Whether such procedures offer advantages over the IIF test will be determined in a prospective clinical study.